Pandangan Fuqaha Mutaqaddimīn dan Muta’akhkhirīn Mengenai Isu Akad Nikah Secara Atas Talian: Mutaqaddimīn and Muta’akhkhirīn’s Views on the Issue of Online Marriage Contract - Azhari, Raihanah; Ismail, Ahmad Uzair Izzuddin; Muhammad Daud, Zakiul Fuady (Jurnal Fiqh, 2021)
Marriage is considered a sacred contract that justify the relationship between a man and a woman. For that reason, the practice of it must abide by the predefined terms and regulations to ensure it is legal according to the Islamic law. Under normal circumstances, solemnization is done based on the defined procedures that obey the pillars of marriage, namely formal exchange of ījāb and qabūl, presence of two witnesses, the woman’s guardian, and both the groom and bride. However, along with the convenient technological advances, there are a few mechanisms used to tie the marriage knot online. The practice of tying the knot online has been used widely, specifically during the time of Covid-19 pandemic. Following this, the validity of online solemnization has become a topic discussed among the scholars. This article discusses the viewpoints of Islamic jurists (fuqaha’) including the mutaqaddimīn and muta’akhkhirīn regarding the validity of online solemnization. This qualitative research uses literature review and documentation as the method to collect all the data needed. The research found that some of the muta’akhkhirīn jurists necessitate online solemnization, given that the practice of it obey the defined terms, and some do not. While majority of mutaqaddimīn jurists, except for Ḥanafi jurists, show tendency in not allowing online solemnization.